Management of T1G3 Transitional Cell Carcinoma of Urinary Bladder with Intravesical Bacillus Calmette-Guerin (BCG): Our Experience - Aamir Ali, Naveed Ahmed Shaikh, Amir Ghani, Riaz Hussain, Sanaullah Metlo, Nisar Ahmed Shaikh, Amanullah Abassi, (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To determine efficacy of BCG in T1G3 urinary bladder tumors at department of urology Chandka Medical College Larkana. Patients and Methods: This is retrospective study, patient were selected from hospital record from July 2016 to June 2022. Around 80 included in our study group who were treated in our department for management of high grade non-muscle invasive bladder tumor. After following inclusion and exclusion criteria TURBT were performed and BCG was installed intravesically for induction and maintenance purpose. Patients were followed for 5 years and data was collected on study specific proforma. Results: 80 patients were included in our study with mean age 35year +5.5 SD. Transurethral resection of urinary bladder tumor was performed in all patients with bladder growth. Induction and maintenance instillation of bacillus Calmette-Guerin (BCG) therapy was given to all. The recurrence was noted in 5 patients (6.25%) and the progression was also seen in these 5 patients (6.25%). Disease-specific survival is 93.75% at the follow-up of 5 years. As prevalence of ca bladder is increasing day by day and bladder is sole organ for storing urine so nowadays strategies of treatment is bladder saving surgery. So patient will feel comfortable with natural bladder and on other hand it will minimize complication related to artificially generated urinary bladder. Conclusion: Maintenance BCG therapy for T1G3 bladder tumors is an effective treatment, with satisfactory results and bladder preservation. Keywords: Ca bladder, intravesival chemotherapy, BCG, T1G3 and management.